2008
DOI: 10.1093/rheumatology/ken345
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cartilage contact deformation in the healthy human tibiofemoral joint

Abstract: These data may provide base-line knowledge for investigating the effects of various knee injuries on joint contact biomechanics and the aetiology of cartilage degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 53 publications
9
127
6
Order By: Relevance
“…They reported that healthy subjects have a medial to lateral tibiofemoral contact area ratio of %1.55 between 0 and 15 of knee flexion. In vivo tibiofemoral cartilage contact deformation was also greater in the medial compartment than the lateral compartment during a single-leg lunge activity (28). The larger contact area in the medial compartment appears to be associated with the geometry of the tibiofemoral articular cartilage, with the medial compartment having a larger contact congruity due to the concave medial tibial plateau compared to the convex lateral tibial plateau (29).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that healthy subjects have a medial to lateral tibiofemoral contact area ratio of %1.55 between 0 and 15 of knee flexion. In vivo tibiofemoral cartilage contact deformation was also greater in the medial compartment than the lateral compartment during a single-leg lunge activity (28). The larger contact area in the medial compartment appears to be associated with the geometry of the tibiofemoral articular cartilage, with the medial compartment having a larger contact congruity due to the concave medial tibial plateau compared to the convex lateral tibial plateau (29).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Combination of MR imaging and double fluoroscopy on knees during motion and various flexion angles show similar results (in healthy subject [16][17][18][19] and in subjects with torn cruciate ligaments [19][20][21] ). On the contrary, gaps among the joint surfaces are a common observation in knee arthroscopic operations.…”
Section: -3mentioning
confidence: 69%
“…It should be mentioned that, the patient should be asked to avoid any strenuous activity such as running, lifting and stairclimbing at least 4 hrs prior to the examination. In addition, the patient should be asked to refrain from weight bearing for 1 hr prior the imaging to ensure the knees cartilages are totally recovered from any residual deformation (Bingham et al, 2008).…”
Section: Discussionmentioning
confidence: 99%